A simple route toward next-gen green energy storage concept by nanofibres-based self-supporting electrodes and a solid polymeric design. (October 2016) - Zolin, L.; Nair, Jijeesh R.; Beneventi, D.; Bella, F.; Destro, M.; Jagdale, P.; Cannavaro, I.; Tagliaferro, A.; Chaussy, D.; Geobaldo, F.; Gerbaldi, C.
Abstract: A novel, unique, truly-solid Li-ion cell structural design, based on LiFePO4 /graphite electrodes and profoundly ionic conducting polymer electrolyte, is fabricated by exploiting, for the first time, carbonised cellulose nanofibrils as both the conductive binder and the current collector substrate. Moreover, cellulose nanofibrils are used as reinforcing additive for the preparation of the unconventional composite polymer electrolyte separator. The resulting solid polymeric lab-scale Li-ion cell, assembled in a "pouch cell" envelop, shows remarkably stable characteristics upon prolonged cycling at ambient temperature even at high current regimes. By the way, a simple procedure, easily scalable, is optimized for the spray coating and water-based papermaking. As a result, all components can be fully recovered at the end of the cell operational life by taking advantage of a simple water-based paper recycling technique, opening new horizons for the manufacture of sustainable electrochemical energy storage devices. Graphical abstract: